2014
DOI: 10.1016/j.scitotenv.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact time and the use of hydroxypropyl-β-cyclodextrin in the removal of fluorene and fluoranthene from contaminated soils

Abstract: 14Sorption-desorption experiments of fluorene (FLU) and fluoranthene (FLT) in soils 15were carried out and correlated to their removal from aged contaminated soils using 16 aqueous solutions in the absence and in the presence of hydroxypropyl-β-cyclodextrin 17 (HPBCD) as the extraction agent. FLU became more resistant to extraction in aged 18 contaminated soils due to its initial adsorption onto the mineral and amorphous soil 19 organic matter (SOM) domains, sites of lower binding energy from which, due to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 58 publications
3
19
0
Order By: Relevance
“…The pyrene removal from kaolin-rich soil was a fast process and over 50% of pyrene were removed at the mass ratio of 7:3 after reaching equilibrium (4 h). A fast initial increase of the percentage of pyrene extracted was followed by a slower increase, as shown in desorption of pyrene from kaolin, which is consistent with the findings of Morillo [43]. Desorption curves of kaolin-rich soil was fitted to a simple firstorder model (R P 0.98) and the plots of desorption of pyrene from kaolin was fitted to a first-order two-compartment model (R P 0.94).…”
Section: Effect Of Parameters On Desorption Of Pyrene From Clays and supporting
confidence: 86%
“…The pyrene removal from kaolin-rich soil was a fast process and over 50% of pyrene were removed at the mass ratio of 7:3 after reaching equilibrium (4 h). A fast initial increase of the percentage of pyrene extracted was followed by a slower increase, as shown in desorption of pyrene from kaolin, which is consistent with the findings of Morillo [43]. Desorption curves of kaolin-rich soil was fitted to a simple firstorder model (R P 0.98) and the plots of desorption of pyrene from kaolin was fitted to a first-order two-compartment model (R P 0.94).…”
Section: Effect Of Parameters On Desorption Of Pyrene From Clays and supporting
confidence: 86%
“…These diuron solubility studies in the aqueous phase in the presence of different CDs showed that the best complexation parameters for the formation of CD-diuron water-soluble inclusion complexes were obtained in the case of HPBCD. CDs are considered novel hosts for the complexation of hydrophobic compounds in the environment, including PAHs and pesticides and even some emerging contaminants such as alkylphenols (Morillo et al, 2014;Sánchez-Trujillo et al, 2013). Consequently, the use of CDs can address some of the largest problems facing chemistry, such as the increase of pollution in the environment (Albelda et al, 2012).…”
Section: Effect Of Hpbcd On Soil Diuron Mineralisationmentioning
confidence: 99%
“…The calculated K S (1:1) was 484M -1 , which is within the range considered suitable for the formation of stable inclusion complexes 100-5000M -1 [17]. The K S (1:1) calculated by Filipović-Grcić J et al [12] was equal to 466M -1 . The relation between S max = 4.9338mM and S o = 0.0769mM, demonstrated that the increase of HA solubility was on the order of 64 times.…”
Section: Determination Of Stoichiometry Apparent Stability Constant mentioning
confidence: 84%
“…The HPβCD which is known for its good aqueous solubility and low toxicity [11] and the cost is within the range of common surfactants [12].…”
Section: Introductionmentioning
confidence: 99%